Association of Hashimoto’s thyroiditis and anti-thyroid antibodies with oral lichen planus: A cross-sectional study - Zhang, Tianyu; Hou, Feifei; Liu, Dan; Zhou, Hangfan; Sun, Yutong; Deng, Xiaoting; Xu, Yiming; Xiao, Yanxuan; Wang, Xianwen; Wu, Chuanji; Meng, Yang; Yuan, Peiyang; et al. (Frontiers in Immunology, 2022)
Hashimoto’s thyroiditis (HT) and its autoantibodies may be associated with oral lichen planus (OLP). In this cross-sectional study, we aimed to assess the relationship among HT, auto-anti-thyroid antibodies, and OLP in a Chinese population of 247 patients with oral lichen planus. Clinical manifestations of OLP were evaluated using the Thongprasom scoring system and clinical type. The diagnosis of HT was based on thyroid function, anti-thyroid peroxidase antibody (anti-TPOAb) and anti-thyroglobulin antibody (anti-TgAb) detection, and ultrasonography. The prevalence of HT in all patients with OLP was 39.68% (98/247); the prevalence in females with OLP was 46.24% (86/186), which was higher than that in males with OLP 19.67% (12/61) (P < 0.01). The titers of the two HT autoantibodies in females with OLP were higher than those in males (P < 0.01). The clinical manifestations of OLP, regardless of being evaluated using the Thongprasom system or clinical type, were not significantly associated with HT development or TPOAb (P = 0.864) or TgAb titers (P = 0.745). In this population-based southern Chinese cohort, the prevalence of HT in patients with OLP, particularly in female patients with OLP, was significantly higher than that in the general population. Female patients had higher HT autoantibody titers than male patients. However, the clinical manifestations of OLP were not significantly correlated with either HT development or auto-anti-thyroid antibody levels. The findings could help further elucidate the factors involved in the relationship between oral lichen planus and Hashimoto’s thyroiditis.